2017
DOI: 10.1016/j.jsps.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

An overview of pharmacodynamic modelling, ligand-binding approach and its application in clinical practice

Abstract: The study of the magnitude and variation of drug response is defined as pharmacodynamics (PDs). PD models examine plasma concentration and effect relationship. It can predict the archetypal effect ([Formula: see text]) of a drug as a function of the drug concentration ([Formula: see text]) and estimate an unknown PD parameter ([Formula: see text]). The PD models have been described as fixed, linear, log-linear, [Formula: see text], sigmoid [Formula: see text], and indirect PD response. Ligand binding model is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
103
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 20 publications
5
103
0
1
Order By: Relevance
“…The K D for the assessment of the DENV-2 E-proteins towards Au/IgM and Au/DSU/ NH 2 rGO-PAMAM/IgM were then calculated and found to be 1.1306 pM; R 2 = −0.5 and 0.1496 pM; R 2 = 0.99, respectively. The obtained K D values are found to be consistent with the standard K D value for protein interaction (K D < 10 nM) 92,93 . The smaller K D value revealed that the Au/DSU/NH 2 rGO-PAMAM/IgM sensor film has higher affinity (K A ) interaction towards DENV E-proteins compared with Au/IgM sensor film.…”
Section: Sensitivity and Binding Affinity Of Dsu/nh 2 Rgo-pamam/igm Ssupporting
confidence: 80%
“…The K D for the assessment of the DENV-2 E-proteins towards Au/IgM and Au/DSU/ NH 2 rGO-PAMAM/IgM were then calculated and found to be 1.1306 pM; R 2 = −0.5 and 0.1496 pM; R 2 = 0.99, respectively. The obtained K D values are found to be consistent with the standard K D value for protein interaction (K D < 10 nM) 92,93 . The smaller K D value revealed that the Au/DSU/NH 2 rGO-PAMAM/IgM sensor film has higher affinity (K A ) interaction towards DENV E-proteins compared with Au/IgM sensor film.…”
Section: Sensitivity and Binding Affinity Of Dsu/nh 2 Rgo-pamam/igm Ssupporting
confidence: 80%
“…Besides studying the apparently proinflammatory effect of uric acid on macrophages, we also wanted to explore the molecular mechanism that is potentially involved. In our study, the production of TNF-alpha, TLR4, and CD11c in response to uric acid exhibited a typical dose-response relationship, where a maximum effect is found and, beyond this point, a plateau can be seen, which indicates saturation and the abolishment of the observed effect [47]. The dose-response relationship has been attributed to the interaction between ligand and its receptor [47,48], which suggested to us the possible involvement of a molecule able to transport uric acid inside the macrophage, as is the case of URAT1.…”
Section: Discussionsupporting
confidence: 58%
“…As previous study has shown that self-efficacy belief may have a positive effect on academic achievement, Snyder's theory-based group hope therapy is hypothesized to improve academic self-efficacy beliefs. In the present study, the effectiveness of Snyder's theory-based group hope therapy was tested over time and the association between hope, confidence in ability to do homework in classroom, confidence in ability to do homework in outside classroom, confidence in ability to interact with others in university, and confidence in ability to manage work, family and university was investigated (Aliverti et al, 2017;Bich et al, 2017;Elsadek et al, 2017;Oskay et al, 2017;Salahudeen and Nishtala, 2017;Ujwala and Babu, 2017).…”
Section: Study Aims and Hypothesesmentioning
confidence: 99%